ANALISIS PENGARUH STATUS KEPEGAWAIAN DAN MOTIVASI TERHADAP KINERJA - Bambang NS (Panorama Nusantara, 2015)
The purpose of this study was to determine the effect of variable employment status and motivation partially on student performance (a case study in Jakarta students STEIN). This study is a survey research using quantitative descriptive methods and questionnaires as a data collection tool. The location of this research object is the Jakarta International School of Economics with a sample that used as many as 70 people. The results obtained are contained partially and simultaneously influence between the variables employment status and motivation of the student's performance STEIN.